2010
DOI: 10.1016/j.ydbio.2010.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog signaling induces arterial endothelial cell formation by repressing venous cell fate

Abstract: In vertebrate embryos, the dorsal aorta and the posterior cardinal vein form in the trunk to comprise the original circulatory loop. Previous studies implicate Hedgehog (Hh) signaling in the development of the dorsal aorta. However, the mechanism controlling specification of artery versus vein remains unclear. Here, we investigated the cell-autonomous mechanism of Hh signaling in angioblasts (endothelial progenitor cells) during arterial-venous specification utilizing zebrafish mutations in Smoothened (Smo), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
48
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 43 publications
3
48
2
Order By: Relevance
“…Supporting this theory, the DA and CV emerge by direct migration of two separate sources of progenitor cells in two independent waves from the lateral plate mesoderm (Williams et al, 2010;Kohli et al, 2013). However, it has also been reported that the CV forms via segregation from the DA (Herbert et al, 2009).…”
Section: Introductionmentioning
confidence: 81%
“…Supporting this theory, the DA and CV emerge by direct migration of two separate sources of progenitor cells in two independent waves from the lateral plate mesoderm (Williams et al, 2010;Kohli et al, 2013). However, it has also been reported that the CV forms via segregation from the DA (Herbert et al, 2009).…”
Section: Introductionmentioning
confidence: 81%
“…The patterning of the trunk vasculature in the zebrafish is directed by a number of different cues. Signaling from midline structures is necessary for primary vascular patterning of the trunk dorsal aorta and cardinal vein (Zhong et al, 2000;Zhong et al, 2001;Lawson et al, 2003;Hong et al, 2006;Swift and Weinstein, 2009;Williams et al, 2010), whereas positive and negative somite-derived molecules subsequently regulate the angiogenic growth of trunk intersegmental and parachordal vessels (Torres-Vazquez et al, 2004;Pollard et al, 2006;Wilson et al, 2006;Jones and Li, 2007). These and other recent findings point to the important role of locale-specific patterning mechanisms for blood vessels.…”
Section: Introductionmentioning
confidence: 91%
“…Furthermore, VEGF signaling has been shown to act upstream of the Notch pathway during arterial differentiation . A more recent report also suggests a direct involvement of the Hedgehog pathway in arterial differentiation (Williams et al, 2010). Thus, Sonic hedgehog, VEGF and Notch are necessary for proper arterial gene expression and the separation of arteries and veins.…”
Section: Introductionmentioning
confidence: 94%